39 Valve-in-valve transcatheter aortic valve implantation in trifecta aortic bioprostheses – a single centre experience. (4th June 2021) - Shah, Benoy; Haider, Syed; Rawlins, John; Calver, Alison; Corbett, Simon; Rakhit, Dhrubo; Ohri, Sunil; Curzen, Nick
Abstract : Introduction: Valve-in-valve transcatheter aortic valve implantation (V-in-V TAVI) has become an increasingly popular alternative to re-do surgery for patients with failing aortic bioprosthetic valves. The Trifecta aortic valve replacement (AVR), designed for supra-annular insertion, consists of a titanium stent with externally mounted leaflets fashioned from bovine pericardium. Several studies have reported premature structural degeneration of the Trifecta valve. There are currently few data regarding the feasibility & efficacy of V-in-V TAVI within Trifecta bioprostheses. Methods: This represents a retrospective review of prospectively collected data at our centre for TAVI procedures performed between January 1st 2015 and December 31st 2020 inclusive. In cases of V-in-V TAVI to treat a failing Trifecta valve, we collected demographic, procedural, echocardiographic and short-term follow-up data from electronic records systems for both this NHS Trust and primary care. Results: Over a 6-year period, we performed 549 TAVI procedures, of which 51 (9.3%) were V-in-V cases. Of these 51, 15 (29%) were for patients with failing Trifecta valves (9 female, mean age 80.9 ± 5.6yrs;. predominant stenosis in 5 & transvalvular regurgitation in 10). Figures 1 & 2 demonstrate examples of prosthesis stenosis & prosthesis regurgitation treated by V-in-V TAVI. The median time from original AVR to V-in-V TAVI procedure was 59 months (IQR 36.5, range 16–93 months). All procedures were performed via the transfemoral route and 13/15 under conscious sedation. A balloon-expandable TAVI valve was used in 14 patients & a self-expanding valve in 1 patient. Post-procedural echocardiography revealed a mean aortic peak velocity 2.9 ± 0.4m/s & mean aortic gradient 19 ± 5mmHg. Paravalvular aortic regurgitation was absent in 7 cases, trivial in 6 & mild in 2 patients. In-hospital and 30-day mortality were 0%. There were three deaths during follow-up (36, 14 & 3 months post procedure), all of which were non-cardiac in nature. Conclusion: V-in-V TAVI is a safe and feasible alternative to re-do surgical AVR for patients with a failing Trifecta aortic bioprosthesis. Unlike other bioprosthetic valves, the Trifecta valve cannot be fractured to enable a larger V-in-V TAVI valve to be implanted. Thus, longer term follow-up of such patients will allow a full understanding of the long-term haemodynamic and clinical outcomes in this patient cohort. Conflict of Interest: Nil